(untitled) (Medical Forum Monthly, 2021)
Objective: Resistin is a 12-Kd protein synthesized and secreted in adipose tissue. It is member of C-terminal cysteine rich protein family. Serum resistin levels increase in chronic inflammatory conditions. In the current study, the levels of serum resistin were estimated in healthy, interferon (IFN) treated and untreated groups of Hepatitis C (HC) to assess its role as inflammatory biomarker. Resistin is said to be affected in diabetes mellitus. Study Design: Analytical study Place and Duration of Study: This study was conducted at the Department of Physiology and Cell Biology, University of Health Sciences Lahore from May 2013 to November 2015. Materials and Methods: 28non-diabetic subjects of both sexes were recruited in each group and compared within the groups (Control, Untreated and Treated HC patients). PCR was done for viral load. Serum resitin was measured by using ELISA. Results: Mean serum levels of resistin were higher in untreated HC patients as compared to INF treated HC patients but the difference was not significant. However, significant difference was observed among the males and females of untreated HC group in which males had higher values than females. Conclusion: Serum resistin levels are lower in healthy and INF treated individuals as compared with the untreated subjects or hepatitis C. However, the difference was not significant but similar study with larger sample size is recommended to establish cause effect relationship.